Relationship Between Ovary Size and Anti-Müllerian Hormone Levels in Holstein–Friesian Cows - Widodo, Oky Setyo; Nishihara, Saeki; Pambudi, Dhidhi; Kusakabe, Ken Takeshi; Taura, Yasuho; Nishi, Yasunobu; Yamato, Osamu; Taniguchi, Masayasu; Takagi, Mitsuhiro (Frontiers in Veterinary Science, 2022)
The aim of this study was to verify the association between ovarian size and blood AMH levels in HF cows. Sixty multiparous HF cows from three herds were included in this study. The data required for calculating the ovarian volume included the “major axis (length),” “minor axis (width),” and “thickness” of the ovary. All ultrasonography (US) images were acquired at the outermost ends/poles of both the ovaries and of the follicles (>8 mm) and corpus luteum (CL); concomitantly, the blood was sampled from the jugular or coccygeal vein. Based on the ovarian images of each cow, the following ovarian size patterns were calculated using an image analysis software: (1) total area of both the left and right ovaries, (2) individual size of the large ovary, and (3) individual size of the small ovary. For each ovary area pattern, two properties were assessed: (A) presence of follicles (>8 mm) and CL, which may not secret AMH, in the ovaries and (B) absence of follicles (>8 mm) and CL in the ovaries. Serum AMH levels were measured using enzyme-linked immunosorbent assay. The correlation between ovary size and serum AMH levels was measured in terms of the aforementioned patterns and was evaluated statistically. The results of our preliminary study with ovaries from slaughter-house cows (n = 22) revealed that the “thickness” of the ovary was not necessary for estimating ovarian volume and that length and width were sufficient. A strong correlation was observed among ovarian length, width, and thickness (r > 0.96). No significant difference was observed (p > 0.05) in the mean ages or parities among the three herds. Among the ovary sizes measured in this study, the highest correlation was found between the total size of an individual large ovary (including follicular and luteal size) and AMH levels (r = 0.387, p = 0.002). This is the first study to demonstrate the correlation between total size of individual large ovaries and serum AMH levels in HF cows. US observations of the ovaries will allow for estimation of differences in AMH levels and help predict ovarian activity and superovulation performance of cows.